2019
DOI: 10.1177/0145561319862212
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Utilizing Smartphone Flashlights as an Alternative Endoscopic Light Source in Emergency Situations

Abstract: Although the image quality from modern distal chip endoscopes is superior, limited mobility of the endoscopic tower prevents this technology from being used in inpatient and emergency departments. In these settings, otolaryngologists commonly use older flexible laryngoscopes with portable light sources. However, these light sources could malfunction. Smartphones are ubiquitous nowadays, and the smartphone’s flashlight may be used alternatively to provide illumination when primary light malfunctions. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Table 1. [9] Resolve the emergency not fixed, not centered, need assistant Milner [10] Resolve the emergency not fixed, not centered, need assistant Deshmukh [11], [12] Resolve the emergency not fixed, not centered, need assistant Ray [13] Resolve the emergency not fixed, not centered, need assistant Davidson [14] Resolve the emergency not fixed, not centered, need assistant Butler [15] Resolve the emergency not fixed, not centered, need assistant…”
Section: Test and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1. [9] Resolve the emergency not fixed, not centered, need assistant Milner [10] Resolve the emergency not fixed, not centered, need assistant Deshmukh [11], [12] Resolve the emergency not fixed, not centered, need assistant Ray [13] Resolve the emergency not fixed, not centered, need assistant Davidson [14] Resolve the emergency not fixed, not centered, need assistant Butler [15] Resolve the emergency not fixed, not centered, need assistant…”
Section: Test and Resultsmentioning
confidence: 99%
“…Davidson et al Figure 2(f) demonstrated the feasibility of using the smartphone for short cystoscopy in poor or developing countries (LMICs) after the light source lamp went out in the absence of spare with an iPhone 6 that generated enough illumination to do the exam [14]. By comparing conventional light sources, namely stryker 8000 and storz 1130103 and galaxy S6 and S7 smartphones, and iPhone 4, 6, 8 and X; Butler et al Figure 2(g) concluded the feasibility of using the flashlight for flexible laryngoscopy [15]. The structure of this work is as follow: The first section focuses on the working principle, designing and discussion.…”
Section: An Innovative Adapter To Use Smartphone Flashlight As a Light Source For Endoscopy In Emergency And Lmicsmentioning
confidence: 99%